How PrEP delivery was integrated into public ART clinics in central Uganda: A qualitative analysis of implementation processes - Wyatt, Monique A; Pisarski, Emily E; Nalumansi, Alisaati; Kasiita, Vicent; Kamusiime, Brenda; Nalukwago, Grace K; Thomas, Dorothy; Muwonge, Timothy R; Mujugira, Andrew; Heffron, Renee; Ware, Norma C (Public Library of Science, 2024)
Tailored delivery strategies are important for optimizing the benefit and overall reach of PrEP in sub-Saharan Africa. An integrated approach of delivering time-limited PrEP in combination with ART to serodifferent couples encourages PrEP use in the HIV-negative partner as a bridge to sustained ART use. Although PrEP has been delivered in ART clinics for many years, the processes involved in integrating PrEP into ART services are not well understood. The Partners PrEP Program was a stepped-wedge cluster randomized trial of integrated PrEP and ART delivery for HIV serodifferent couples in 12 public health facilities in central Uganda (Clinicaltrials.gov NCT03586128). Using qualitative data, we identified and characterized key implementation processes that explain how PrEP delivery was integrated into existing ART services in the Partners PrEP Program. In-depth interviews were conducted with a purposefully-selected sub-sample of 83 members of 42 participating serodifferent couples, and with 36 health care providers implementing integrated delivery. High quality training, technical supervision, and teamwork were identified as key processes supporting providers to implement PrEP delivery. Interest in the PrEP program was promoted through the numerous ways health care providers made integrated ART and PrEP meaningful for serodifferent couples, including tailored counseling messages, efforts to build confidence in integrated delivery, and strategies to create demand for PrEP. Couples in the qualitative sample responded positively to providers’ efforts to promote the integrated strategy. HIV-negative partners initiated PrEP to preserve their relationships, which inspired their partners living with HIV to recommit to ART adherence. Lack of disclosure among couples and poor retention on PrEP were identified as barriers to implementation of the PrEP program. A greater emphasis on understanding the meaning of PrEP for users and its contribution to implementation promises to strengthen future research on PrEP scale up in sub-Saharan Africa.
Keywords: HIV; Antiretroviral therapy ; Pre-exposure prophylaxis; Health care facilities; Health care providers; Uganda; Public and occupational health; HIV prevention